Comparing the Effect of Cooling Gel Pad and Non-Nutritive Sucking on Pain during Hepatitis Vaccination in Newborn Infants: A Randomized Controlled Clinical Trial - Hadi Najafi; Hasan Boskabadi; Maryam Salari; Soheila Karbandi (Journal of Mazandaran University of Medical Sciences, 2019)
Background and purpose: The most common painful procedures in neonates is blood sampling and vaccination. The pain of vaccination is short and mild, but it could have long-term complications. This study aimed at comparing the effects of local cold and non-nutritive sucking on pain caused by vaccination in neonates. Materials and methods: A clinical trial was performed in 113 term neonates. They were randomly divided into three groups. In first group, cooling gel was placed on the local site for 90 seconds and vaccination was done thereafter. In second group, sucking of finger was performed for two minutes before injection. Vaccination in control group was carried out without any intervention. Neonatal infant pain scale (NIPS) was used to measure pain and crying time was evaluated using a chronometer. Data were analyzed by Mann-Whitney, Chi-square, independent t-test, and repeated measure using SPSS V16. Results: There were significant differences between the three groups in pain intensity at the time of needle insertion (P= 0.002) and within 30 seconds (P= 0.0001). This difference was seen between the group with cooling gel and controls and non-nutritive sucking group and controls. There was no significant difference between the three groups in duration of crying (P= 0.454). However, the mean crying time in the cooling gel group (39.8 seconds) was lower than non- nutritive sucking group (42.3 seconds) and controls (52.7 seconds). Conclusion: Both methods of local cold and non-nutritive sucking are helpful in reducing pain intensity. This intervention is practical and easy which could minimize the negative impact of pain in neonates.